Alih Fungsi Bahu Jalan sebagai Lahan Parkir di Kabupaten Lumajang - Abadi, Erwin Firman; Ubaidillah, Luthfian (Al-DYAS, 2024)
Indonesia, as the largest economy in Southeast Asia, has witnessed significant infrastructure development driven by government efforts to foster sustainable economic growth. This development, particularly in urban areas, has led to increased land demand and the repurposing of public spaces. Lumajang Regency in East Java Province, known for its tourism and mining potential, has experienced substantial population growth, with a 9.37% increase between 2018 and 2022, according to the Central Statistics Agency. This growth has heightened the need for adequate infrastructure, including parking facilities. This study investigates the local government's policy on the repurposing of road shoulders for parking in Lumajang Regency. Employing a normative legal research method, the study examines relevant laws and regulations, including primary legal materials such as the 1945 Constitution of the Republic of Indonesia, Law No. 22 of 2009 on Road Traffic and Transportation, and specific local regulations in Lumajang Regency. The findings indicate that the unauthorized use of road shoulders as parking spaces, especially on Jalan Jend. S. Parman and Jalan Alun-Alun Utara, has caused significant inconvenience and traffic congestion. The study emphasizes the need for proper implementation of parking regulations, including the installation of appropriate signage and road markings, as required by law. The research concludes that the misuse of road shoulders for parking contravenes existing regulations, highlighting the urgent need for improved enforcement of parking policies in Lumajang Regency to manage traffic flow and public convenience effectively.